Unraveling Mechanisms and Impact of Microbial Recruitment on Oilseed Rape (Brassica napus L.) and the Rhizosphere Mediated by Plant Growth-Promoting Rhizobacteria - Ying Liu; Jie Gao; Zhihui Bai; Shanghua Wu; Xianglong Li; Na Wang; Xiongfeng Du; Haonan Fan; Guoqiang Zhuang; Tsing Bohu; Xuliang Zhuang (Microorganisms, 2021)
Plant growth-promoting rhizobacteria (PGPR) are noticeably applied to enhance plant nutrient acquisition and improve plant growth and health. However, limited information is available on the compositional dynamics of rhizobacteria communities with PGPR inoculation. In this study, we investigated the effects of three PGPR strains, Stenotrophomonas rhizophila, Rhodobacter sphaeroides, and Bacillus amyloliquefaciens on the ecophysiological properties of Oilseed rape (Brassica napus L.), rhizosphere, and bulk soil; moreover, we assessed rhizobacterial community composition using high-throughput Illumina sequencing of 16S rRNA genes. Inoculation with S. rhizophila, R. sphaeroides, and B. amyloliquefaciens, significantly increased the plant total N (TN) (p < 0.01) content. R. sphaeroides and B. amyloliquefaciens selectively enhanced the growth of Pseudomonadacea and Flavobacteriaceae, whereas S. rhizophila could recruit diazotrophic rhizobacteria, members of Cyanobacteria and Actinobacteria, whose abundance was positively correlated with inoculation, and improved the transformation of organic nitrogen into inorganic nitrogen through the promotion of ammonification. Initial colonization by PGPR in the rhizosphere affected the rhizobacterial community composition throughout the plant life cycle. Network analysis indicated that PGPR had species-dependent effects on niche competition in the rhizosphere. These results provide a better understanding of PGPR-plant-rhizobacteria interactions, which is necessary to develop the application of PGPR.